VALIDITAS DAN PRAKTIKALITAS LEMBAR KEGIATAN MAHASISWA ELEKTRONIK (LEKEMANIK) BERMUATAN ETNOSAINS PADA MATERI PTERIDOPHYTA - Awal, Raudhah; Yasmin, Khairani; Sari, Ermina (Universitas Lancang Kuning, 2024)
Innovation of student activity sheets in electronic form by integrating the culture of the local community becomes an efficient and effective learning alternative. This study aims to examine the validity and practicality of electronic student activity sheets (LEKEMANIK) containing ethnoscience on pteridophyta material. This development research model consists of 4 main stages, namely: definition, design, development, and deployment. The data collection instrument was a questionnaire given to material experts, media experts and linguists whose aim was to determine the validity of the LEKEMANIK. Practicality questionnaire instruments were given to supporting lecturers and students. This research produced a product in the form of an electronic student activity sheet containing ethnoscience on pteridophyta material with the results of an assessment from material experts obtained a score of 90% with Very valid criteria, an assessment from media experts obtained a score of 82% with Very valid criteria and an assessment from linguists obtained a score of 83, 33% with Very Valid criteria. The level of practicality of electronic student activity sheets by lecturers is 86.22% with very practical criteria, and for students it is 82.36% with very practical criteria. From the results of the study it can be concluded that the electronic student activity sheet for the subject of lower plant botany with ethnoscience content on pteridophyta material is appropriate to use.